Facets of Machismo and Maternalism in Fictional Philippine Settings - Gilbas, Sherill (JPAIR Multidisciplinary Research, 2014)
The legal implication of infidelity in Philippine law serves as an initial display of “machismo” that reflects the propensity and pervasiveness of its concept in Philippine society. As a response to society’s partiality to male’s gender role, the gender role of women called “maternalism” has surfaced. This gender role identifies itself as a manifestation of society’s concept of gender roles including double-standard machismo. This paper aims to disclose how desire is depicted as justification to the existence of machismo and maternalism in selected Philippine short stories like “Magnificence,” “Of Fish, Flies, Dogs and Women,” “The Chieftest Mourner,” “Thirsty is the Arid Land,” and “Wedding Dance.” This paper also supports the concept of desire with pleasure principle and tripartite model of Sigmund Freud’s psychoanalysis. The paper’s critical point focuses on how infidelity is reflected in said stories, thereby leading to understanding its concept as manifested by characters’ gender roles. This paper also employs the descriptive literary analysis anchored on Hans-Georg Gadamer’s hermeneutics. In addition, the paper also discusses the binary opposition of marriage and infidelity, faithfulness and unfaithfulness, along with its implication to the couple and the society in general. The paper identifies culture as an inherent factor in addressing the questions of gender roles in Philippine fiction.